Methane-Fueled Proton-Conducting Ceramic Fuel Cell Stacks. (30th May 2017) - Ding, Hanping; Le, Long Quoc; Sullivan, Neal P
Abstract : In this paper, we present our efforts on scale up of proton-conducting ceramic fuel cells (PCFCs) from button cells to small stacks. The PCFCs are based on BaCe0.2 Zr0.6 Y0.2 O3-d (BCZY26) electrolyte. Anode-supported membrane-electrode assemblies are fabricated using conventional ceramic-processing techniques, and reach 40 mm in diameter. Multi-cell PCFC stacks are found to generate reasonable power densities at intermediate temperature under direct methane-steam fuel feeds, reaching 258 mW / cm 2 at 0.75 V and 550 ºC.